Adaptation of the Wechsler Preschool and Primary Scale of Intelligence-III and lessons learned for evaluating intelligence in low-income settings. Issue 3 (3rd July 2018) - Rasheed, Muneera A.; Pham, Sofia; Memon, Uzma; Siyal, Saima; Obradović, Jelena; Yousafzai, Aisha K.
ABSTRACT: Many global settings lack indigenous measures of child development, making the adaptation of available instruments necessary. The aim of this study was to reliably adapt the core subtests of the Wechsler Preschool and Primary Scale of Intelligence-III (WPPSI-III) to assess cognitive abilities in young children in rural Pakistan. A systematic adaptation protocol was followed and psychometric properties were tested after completing data collection on a cohort of 1, 273 children at 4 years of age. The results indicated a one-factor structure, and acceptable reliability of the full-scale score implying only this score should be used for any interpretation of results. Lessons learned for adaptation and evaluation in highly disadvantaged contexts are shared.